Photon pairs bi-directionally emitted from a resonant metasurface - Son, Changjin; Sultanov, Vitaliy; Santiago Cruz, Tomás; Anthur, Aravind P. P.; Zhang, Haizhong; Paniagua-Dominguez, Ramon; Krivitsky, Leonid; Kuznetsov, Arseniy I. I.; Chekhova, Maria (Nanoscale, 2023)
Metasurfaces are artificially structured surfaces able to control the properties of light at subwavelength scales. While, initially, they have been proposed as means to control classical optical fields, they are now emerging as nanoscale sources of quantum light, in particular of entangled photons with versatile properties. Geometric resonances in metasurfaces have been recently used to engineer the frequency spectrum of entangled photons, but the emission directivity was so far less studied. Here, we generate photon pairs via spontaneous parametric down conversion from a metasurface supporting a quasi-bound state in the continuum (BIC) leading to remarkable emission directivities. The pair generation rate is enhanced 67 times compared to the case of an unpatterned film of the same thickness and material. At the wavelength of the quasi-BIC resonance, photons are mostly emitted backwards, while their partners, spectrally detuned by only 8 nm, are emitted forwards. This behavior demonstrates fine spectral splitting of entangled photons and their bi-directional emission, never before observed in nanoscale sources. We expect this work to be a starting point for the efficient demultiplexing of photons in nanoscale quantum optics.
CRIS-Team WoS Importer:2023-02-10